PELUANG DAN TANTANGAN KERJASAMA INVESTASI INDONESIA DENGAN NEGARA-NEGARA VISEGRAD - Surya, Aelina; Bukhari, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2019)
This study discusses the opportunities and challenges of investment cooperation between Indonesiaand the Visegrad countries. The author uses the concept of economic diplomacy to explain theseproblems. Indonesia undertakes economic diplomacy efforts with the aim of continuing to increaseits investment cooperation with Visegrad countries. But in its economic diplomacy efforts there areopportunities and challenges that must be faced. The opportunities in this regard are large investmentpotential, similar goals between the two, economic diplomacy that can be carried out to the level oflocal government, and ease of investment in Indonesia. While the challenge is that there is no clearand measurable economic diplomacy blueprint, very far geographical location, and limitedcollaboration in the form of bilateral relations.